2020
DOI: 10.1016/j.cognition.2020.104184
|View full text |Cite
|
Sign up to set email alerts
|

The effect of contextual plausibility on word skipping during reading

Abstract: Recent eye-movement evidence suggests readers are more likely to skip a high-frequency word than a low-frequency word independently of the semantic or syntactic acceptability of the word in the sentence. This has been interpreted as strong support for a serial processing mechanism in which the decision to skip a word is based on the completion of a preliminary stage of lexical processing prior to any assessment of contextual fit. The present large-scale study was designed to reconcile these findings with the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(45 citation statements)
references
References 57 publications
(106 reference statements)
1
43
1
Order By: Relevance
“…However, more recent simulations of stimuli selected to factorially manipulate target length, frequency, and plausibility revealed that E‐Z Reader 10 successfully simulated empirical effects of plausibility on skipping. This suggests that postlexical integration may be at least partially responsible for the preview plausibility effect (Veldre, Reichle, Wong, & Andrews, ).…”
Section: Mechanisms Underlying Parafoveal Preview Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, more recent simulations of stimuli selected to factorially manipulate target length, frequency, and plausibility revealed that E‐Z Reader 10 successfully simulated empirical effects of plausibility on skipping. This suggests that postlexical integration may be at least partially responsible for the preview plausibility effect (Veldre, Reichle, Wong, & Andrews, ).…”
Section: Mechanisms Underlying Parafoveal Preview Effectsmentioning
confidence: 99%
“…The early disruptions to eye movements, including skipping, caused by plausibility violations in the parafovea and the distinct patterns of reanalysis observed in response to semantic and syntactic violations (Veldre & Andrews, ) implicate rapid, incremental, word‐by‐word integration of new input with the developing representation of the sentence (Altmann & Mirkovic, ). When an implausible preview is a short, easy to process word, rapid postlexical integration failure may directly trigger reanalysis processes that influence first‐pass reading, but the timecourse and information requirements of postlexical integration make it unlikely that this mechanism is the sole source of the plausibility preview effect (Veldre et al, ).…”
Section: Conclusion and Implications For The Cognitive Architecture mentioning
confidence: 99%
“…Previous research showed a considerable effect of preview plausibility such that plausible previews resulted in processing benefit, regardless of their semantic links with the target (e.g., [ 83 , 84 ]), and independently of the orthographic relatedness between the preview and target [ 104 ], especially when the previews were not predictable from the immediate preceding context ([ 105 ] also [ 106 ] for additional empirical evidence, and [ 107 ] for a review). In essence, when the upcoming word (in the parafovea) is plausible, the information extracted from it facilitates the incremental sentence processing, regardless of the relatedness between the target and the preview, hence plausible previews generate more skipping of the target (e.g., [ 106 ]), and shorter fixation duration on the target in early processing measures when it is fixated and not skipped (e.g., [ 83 ]). As we have not controlled for target and preview plausibility, the possible effects of plausibility on the reported results were not part of our a priori research question.…”
Section: Discussionmentioning
confidence: 99%
“…Rayner, Warren, Juhasz and Liversedge (2004) found words which were implausible in a given context led to greater processing difficulty in later fixation measures. More recently, implausible words have been shown to affect earlier fixation measures (Staub, Rayner, Pollatsek, Hyönä, & Majewski, 2007) however, evidence suggests that whilst the effects of plausibility may be detectable in early fixation measures, the influence of plausibility on reading may be post-lexical (Abbott & Stuab, 2015;Veldre, Reichle, Wong & Andrews, 2020). When testing our target words for plausibility (see Supplemental Material D for full details of this process and results) we found that each target word was rated most-plausible within its own supportive context.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, Abbott and Staub (2015) found that their LF plausible words were rated as significantly less plausible than their HF counterparts; they noted that such a difference should be expected and presented evidence that plausibility ratings of LF plausible words correlated with log frequency of LF words, whereas no such correlation was found for other word types. Further, in eye movement analysis, previous research (Rayner et al, 2004;Staub et al, 2007;Abbott & Staub 2015;Veldre et al, 2020) generally treats plausibility as a binary factor where a threshold is applied during norming to determine implausible targets. Whilst some of our target words may be less plausible in certain context frames, ratings for non-HP targets (i.e., HF and LF targets) do not suggest these words were implausible.…”
Section: Discussionmentioning
confidence: 99%